R-matrix method and the nonlocal nucleon optical potential - Loan, Doan Thi; Phuc, Nguyen Hoang; Khoa, Dao Tien (Communications in Physics, 2018)
The calculable R-matrix method is applied to solve the Schr ̈odinger equation in the optical model (OM) analysis of the elastic nucleon-nucleus scatter- ing using a nonlocal nucleon optical potential (OP). The phenomenological nonlocal nucleon OP proposed by Perey and Buck (PB), and the two recent versions of the PB parametrization were used in the present OM study of the elastic nucleon scattering on 208 Pb and 27 Al targets at different energies. The comparison of the OM results given by the calculable R-matrix method with those given by other methods confirms that the calculable R-matrix method is an efficient tool for the OM study of the elastic nucleon-nucleus scattering using a nonlocal nucleon OP.